Le rôle des acteurs et les dynamiques dans l’évaluation scolaire : un éclairage sociologique - Morales-Perlaza, Adriana; Poitras, Dave (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
This article proposes a sociological theoretical framework to analyze and better understand theoretically the roles of the actors taking part in the processes of assessment activities at school. This proposal is based on a narrative review of 24 French-language studies. The normative paradigm underlines the importance of social structures with regard to the actions of actors and makes it possible to understand the institutionalization and homogenization of assessment activities. The social actor paradigm highlights the reflexivity and knowledge of actors, as well as the way they mobilize institutional structures to achieve their goals. The critical paradigm makes it possible to highlight problematic issues within educational systems, which reproduce social hierarchies at school, as well as the means of transforming them and emancipating the actors. This article contributes to the sociology of school assessment by proposing a framework that allows dialogue between studies in this field.